Specific Characteristics of Digitalization in Medical Education (Texas Journal of Multidisciplinary Studies, 2024)
Information technology (IT) is firmly embedded in all areas of our daily lives. Their implementation in various areas of life is growing rapidly every year. They are becoming an integral part in healthcare, education, and the economy. Informatization is the most important reform mechanism in the medical educational process aimed at improving the quality of knowledge. The development and implementation of IT in education allows us to take informatization to a new level, which will have a beneficial effect on improving the educational process.